The influence of product quality, service quality and ease of use on bni mobile banking customer loyalty, purbalingga regency - Afriani, Lita; Filani, Libran; Puspitaningtias, Rofi; Priyanto, Rofik (Junal Ilmu Manajemen, 2024)
The growing number of financial institutions that focus on the consumer segment has increased the intensity of competition among banks. This situation occurs because banking companies that focus on consumer banking services have a higher level of resilience compared to banks that focus on corporate banking. This research was conducted with the aim of analyzing and determining the influence of product quality and service quality of BNI Purbalingga Regency Branch on customer loyalty as well as determining the influence of the ease of use of BNI Mobile Banking used by customers. Data was obtained by distributing surveys to several respondents. The sample was determined at 60 respondents. This research analysis test uses SPSS with multiple linear regression methods. The results of this research analysis test found that product quality and service quality influence customer loyalty at BNI Purbalingga Regency Branch. Meanwhile, ease of use of BNI Mobile Banking has no effect on customer loyalty at BNI Purbalingga Regency Branch